Political Institutions and Trade Protection - Hein J. Roelfsema (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2004)
Why do levels of trade protection differ so much across countries? Weargue that differences in electoral rules and executive powers mayplay a significant role. We develop a theoretical model and show thatcountries that have a majoritarian electoral system may be moreinclined to have a high level of trade protection. The reason is thatthese countries have fiercer competition for swing districts if comparedto countries that have a proportional electoral system. In the empiricalpart of the paper we show that countries that have a majoritarianelectoral system indeed have higher levels of protection. This result isrobust to various measures of trade protection and to an instrumentalvariables approach that takes account of the endogeneity of politicalinstitutions. We find only weak support for the claim thatpresidentialism reduces trade protection.
Keywords: 330; Trade Policy; Protection; Constitutional Political Economy; Electoral Rules